Online Food Ordering Information System Website-Based: Sistem Informasi Pemesanan Makanan Online Berbasis Website - Priyambodo, Dimas; Hindarto (Universitas Muhammadiyah Sidoarjo, 2021)
Warung Mbak Sih is engaged in the culinary field that serves home cooking such as mixed rice, spicy chicken rice, soup rice, sour rice, fried chicken rice, rawon rice. Lots of customers who buy on the spot or order to be packaged. With the application of ordering food at online stalls, the number of visitors queuing can be limited so that they are not too many. The preparation of the application has been done well by using the HTML and PHP programming languages, as well as the Bootstrap framework. The database used with XAMPP software to manage sata is in the form of the SQL framework Bootstrap language so that it displays good display results both in desktop form and in the form of mobile phone pages. With the ordering application, the time used by buyers at the shop is faster, because orders have been prepared in advance. In addition to ordering the application also displays a variety of good information for stall sales.